The Failure in the Coincidence of Indigenism and Nationalism in the Recognition of Indigenous Villages - Purwadi, Hari; Suryono, Arief; Muslimah, Siti (Faculty of Law, Universitas Jenderal Soedirman, 2023)
This article aims to analyse the challenges of legal functionality as an instrument for transforming indigenous villages from ‘traditional’ to ‘modern.’ This is a post-new-order historical impetus for the coincidence of indigenous and nationalism as a sign of the resurgence of indigenous peoples. In the context of the legal function for social change, the Village Law creates a large gap between traditional and modern villages. This paper is based on the research with the paradigm of law in context and can be categorized as socio-legal research, which perceives law from an interdisciplinary perspective. The results indicate that under the umbrella of the Village Law, the existing legal frameworks fail to achieve the regulatory objectives. Indigenous people's diverse and complex structure throughout Indonesia appears to be less considered. Thus, the laws do not sufficiently stimulate change through the modern indigenous village model.Keywords: indigenous village; legal function; indigenism; indigenous people; nationalism.